Occurrence of white rust (Albugo ipomoeae-panduratae) on Ipomoea acuminata in the brazilian mid-west - Pagani,A.P.S (2012)
Spontaneous plants of Ipomoea acuminata ("morning glory") exhibiting white rust pustules were found in a field crop area of Planaltina, DF, in the fall season of 2010 and the disease causal agent was identified as Albugo ipomoea-panduratae (Oomycota). No reports of the association between A. ipomoea-panduratae and I. acuminata were known in Brazil previously to 2010. A reference specimen was deposited at the University of Brasilia Mycological Reference Collection.